Pistacia Atlantica Extract Enhances Exercise-Mediated Improvement of Antioxidant Defense in Vistar Rats - Parvin Farzanegi; Abbass Ghanbari-Niaki; Abbas Mohseni; Marzieh Haghayeghi (The Society of Aging and Physical Activity (SAPA), 2014)
Exercise training causes increased oxidative stress. Pistacia Atlantica Extract (Mastic) is known to have a protective effect against oxidative stress and inflammation. We examined the effects of exercise training with and without Pistacia Atlantica extract administration on antioxidant markers in vistar rats. Twenty-eight Vistar female rats (six to eight weeks old, 150-200 g weight) allocated into training (n = 14) and control (n = 14) groups and further divided into saline + control (n = 7), saline + training (n = 7), mastic +control (n = 7), and mastic + raining (n = 7). The training groups were given exercise on a treadmill at 25 m/min (0% grade) for 60 min/day, 5 days/week for eight weeks. Mastic groups were administered at a dose 100 mg/kg (7.5 μL/g of body weight), orally. Seventy-two hours after the last training session, the rats were sacrificed and their liver tissues were excised for tissue oxidative stress markers which were detected by ELISA method. Mastic, Exercise, and Exercise+ Mastic attenuated MDA compared to control (p<0.01). Exercise + Mastic showed a stronger suppressive effect than Mastic and exercise. Mastic and Exercise significantly the increase in SOD compared with control (p<0.05). Exercise + Mastic showed further additive effects on increasing SOD (p<0.001). These results suggest that Mastic supplementation and exercise alone induced positive adaptations in modulating oxidant and antioxidant levels without causing the reduced/oxidized glutathione ratio (GSH/GSSG) in liver of vistar rats, but the combined intervention is more effective than either intervention alone.